A tax collector is an assistant to an entrepreneur - Axmedjan Jaksilikov (Peerian Journals Publishing, 2024)
The slogan "Taxman is a helper for an entrepreneur" is a new approach aimed at the development and support of entrepreneurship in the economy of Uzbekistan. The main goal of this approach is to help entrepreneurs choose tax regimes, pay taxes, submit reports and solve problems. Entrepreneurship plays an important role in the economic development of the country and the well-being of the society. Entrepreneurs create new jobs, foster innovation and stimulate economic growth. At the same time, the relationship between the taxman and the businessman is very important. This article talks about how a tax accountant can be an assistant to an entrepreneur.
Keywords: Tax; entrepreneur; economic; innovation